Radiative transition wavelengths and lifetimes for the quintet states in Be-like ions. (May 2019) - Li, Kai kai; Gou, Bing cong
Highlights: Relativistic energies, oscillator strengths and the radiative transition rates of the 1 s 2 l 2 l ′3 l ′′ 5 L e, o ( l  =  s, p; l ′ =  p; l ″ =  s, p, d; L  =  P, D ) states for the Be-like ions are calculated. The fine structure splitting values for the multiply excited quintet states are reported and discussed along with the increase of atomic number z. The radiative transition wavelengths and lifetimes for the multiply excited quintet states are calculated and compared with experimental results. Abstract: Radiative properties of 1 s 2 l 2 l ′3 l ′′ 5 L e, o ( l  =  s, p; l ′ =  p; l ″ =  s, p, d; L  =  P, D ) states are studied using multi-configuration Rayleigh–Ritz method from Z  = 7 to 14. Absolute energies including mass polarization and relativistic corrections are reported for the first time. The contribution of quantum electrodynamics and nuclear field shifts to the total energy is estimated. The variation of the fine structure splitting values with the configuration structure and with the nuclear charge number Z is discussed. The oscillator strengths and the radiative transition rates are calculated using nonrelativistic wave functions. The calculated wavelengths and lifetimes are compared with the theoretical and experimental references.